The Role of Behavioral Science in Personalized Multimodal Prehabilitation in Cancer - Grimmett, Chloe; Bradbury, Katherine; Dalton, Suzanne O.; Fecher-Jones, Imogen; Hoedjes, Meeke; Varkonyi-Sepp, Judit; Short, Camille E. (Frontiers in Psychology, 2021)
Multimodal prehabilitation is increasingly recognised as an important component of the pre-operative pathway in oncology. It aims to optimise physical and psychological health through delivery of a series of tailored interventions including exercise, nutrition and psychological support. At the core of this prescription is a need for considerable health behaviour change, to ensure patients are engaged with and adhere to these interventions and experience the associated benefits. To date the prehabilitation literature has focused on testing the efficacy of devised interventions with a primary focus on physiological and mechanistic outcomes with little consideration for the role of behavioural science, supporting individual behaviour change or optimising patient engagement. Changing health behaviour is complex and to maximise success, prehabilitation programs should draw on latest insights from behavioural science. Behavioural science offers extensive knowledge on theories and models of health behaviour change to further advance intervention effectiveness. Similarly, interventions developed with a person-centred approach, taking into consideration individual needs and preferences will increase engagement. In this article we provide an overview of the extent to which the existing prehabilitation literature incorporates behavioural science, and studies that have explored patient’s attitudes towards and experience with engagement in prehabilitation. We will describe and critique ongoing trials in a variety of contexts within oncology prehabilitation and discuss how current scientific knowledge may be enhanced from a behavioural science perspective. We will also consider the role of ‘surgery schools’ and detail practical recommendations that can be embedded in existing or emerging clinical settings.